Implementing Anti-theft Systems for ATM and Vehicles - H, Mahalakshmi; J, Nikhitha; B, Varsha (Perspectives in Communication, Embedded-systems and Signal-processing - PiCES, 2018)
Anti-theft technology can be implemented on many systems such as ATM, automobiles, mobiles etc. In ATM security we use silent indicate systems, integrated video surveillance cameras, etc. which are all implemented with help of M2M communication technologies. M2M needs new system architecture so we implement a low cost embedded web server based on ARM11 processor and Linux operating system using Raspberry Pi. It has modules such as web enabled control, sensors, shutter lock and camera control. Anti-theft in vehicles can be implemented using GSM and GPS or Bluetooth technologies. In GSM and GPS we install a tracking system and fingerprint verification. This is implemented by single board embedded system equipped with GSM (Global system for mobile) and GPS (Global positioning system). In Bluetooth low energy module we use Arduino board which functions in the master mode and reading of MAC address is done by the BLE slave device. There are several methods used in Anti-theft systems but in this paper we have concentrated more on the following methods.